Modular buck-boost transformerless grid-tied inverter for low voltage solar panels - Nunes, Hugo (2014)
This paper deals with a transformerless AC module for low DC voltage output photovoltaic solar panels. The DC to AC converter was designed to be a single-phase grid-tied inverter, and is based on a buck-boost topology with current mode control to shape the current and to adjust delivered power. The common ground node prevents voltage fluctuations and increases people´s safety. Low power inverters tend to be less efficient than larger ones and are prone to higher harmonic distortion. To overcome these drawbacks, special care was taken in designing the power stage, and harmonic compensation was included in the control stage. The inverter has MPPT capability and operates with unity power factor. Inverter´s operation is analysed, and some simulation results are presented. A 220Wp two-stage single-phase AC module prototype, with 240V and 50Hz sine-wave output, was build and connected to a low voltage photovoltaic solar panel. Experimental results for this plug-and-play converter are here presented.